If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3 + -4x + 5x = x + -3 Combine like terms: -4x + 5x = 1x -3 + 1x = x + -3 Reorder the terms: -3 + 1x = -3 + x Add '3' to each side of the equation. -3 + 3 + 1x = -3 + 3 + x Combine like terms: -3 + 3 = 0 0 + 1x = -3 + 3 + x 1x = -3 + 3 + x Combine like terms: -3 + 3 = 0 1x = 0 + x 1x = x Solving 1x = x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 1x + -1x = x + -1x Combine like terms: 1x + -1x = 0 0 = x + -1x Combine like terms: x + -1x = 0 0 = 0 Simplifying 0 = 0 The solution to this equation could not be determined.
| x+(4+3x)7=0 | | n+6.1=32.1 | | B-32=4(4b+5)-2b | | y+4.5=15.3 | | -a+8-1=1-a | | -8+8n=-2(2-4n) | | lnx=911.28 | | v(6v+1)= | | 11-8z=-12-8z | | -6+n=6 | | x=3785.75-3507 | | 0=6x^3-24x | | G(x)=2f(x-1) | | -6n+4=15 | | g+e=r | | 391=(x+6)-x | | 8-4z=-14-4z | | 5(32)-32=0 | | x-5(4x)+7=35 | | 34=-4r | | 2(x+8)=3(-6) | | I=2000(0.204) | | -5+5x=5x-5 | | X^2+4=134 | | -4=5n-1 | | 14r^3+21r^2-4r-6=0 | | 7q+23=15q-33 | | -x^3-2x^2-3= | | 4x-6+x+3=90 | | I=2000(0.051)(4) | | 6(6-x)-3x=24-6x | | 21m=49 |